2012
DOI: 10.1158/1541-7786.mcr-11-0569
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Stabilizes GAS6/Axl Signaling in Metastatic Prostate Cancer

Abstract: The receptor tyrosine kinase Axl is over-expressed in a variety of cancers and is known to play a role in proliferation and invasion. Previous data from our lab indicates that Axl and its ligand GAS6 may play a role in establishing metastatic dormancy in the bone marrow microenvironment. In the current study, we found that Axl is highly expressed in metastatic prostate cancer (PCa) cell lines PC3 and DU145 and has negligible levels of expression in a non-metastatic cancer cell line LNCaP. Knockdown of Axl in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 45 publications
3
77
0
1
Order By: Relevance
“…Hence, in a hypoxic tumor microenvironment stabilization of AXL expression may underlie driving of metastasis progression [66]. The finding that both AXL and MET are direct targets of HIF-1α/HIF-2α reveals a potent mechanism of hypoxic tumors to sustain malignant phenotypes [62].…”
Section: 2hif-related Transcriptional Activation Of Rtks: Met Axlmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in a hypoxic tumor microenvironment stabilization of AXL expression may underlie driving of metastasis progression [66]. The finding that both AXL and MET are direct targets of HIF-1α/HIF-2α reveals a potent mechanism of hypoxic tumors to sustain malignant phenotypes [62].…”
Section: 2hif-related Transcriptional Activation Of Rtks: Met Axlmentioning
confidence: 99%
“…Transcriptional activation by HIF-1α [49,55] SN12L1 clear cell renal cell carcinoma (ccRCC) cells MET AXL signalling mediated lateral activation by SRC [62] RCC4 ccRCC cells, 786-0 ccRCC cells, HepG2 hepatocellular carcinoma cells, Hep3B hepatocellular carcinoma cells AXL Transcriptional activation by HIF-1α and HIF-2α [62] HLEC lens epithelial cells, PC3 and Du-145 prostate cancer cells AXL Inhibition of GAS6-mediated AXL downregulation [65,66] MCF7, ZR-75, MDA-MB-231 and MDA-MB-468 breast cancer cells RON Transcriptional activation by HIF-1α [69] Numerous cancer types VEGF-A Transcriptional activation by HIF-1α [13,18,23] Rat pulmonary microvascular smooth muscle cells…”
Section: Metmentioning
confidence: 99%
“…The Axl/GAS6 pathway is important for metastasis of several carcinomas [129][130][131][132][133], and is adversely prognostic [134][135][136][137][138]. Axl is necessary for EMT, as evidenced by reduction in mesenchymal biomarkers and increased migration and invasion upon knockdown of Axl in PC cells [139]. GAS6 downregulates expression of its receptor, Axl, and hypoxia is sufficient to prevent GAS6-mediated downregulation of Axl.…”
Section: Microenvironmental Cues As Mediators Of Epmentioning
confidence: 99%
“…Analysis of the array data revealed that HIF-1α regulates multiple genes involved in stem cell maintenance, as discussed above and in Chapter 5. Many other genes we initially identified have since been implicated as being HIF-1α dependent genes such as Angptl4 [72], Jarid1b and the Jumanji proteins [246], several pro-collagens [291] and Axl [245]. However, we also discovered several genes that still had not been previously explored as hypoxiadependent or in the context of breast cancer.…”
Section: A Novel Hif-dependent Gene Involved In Breast Cancer Progresmentioning
confidence: 87%
“…Some of the genes identified have long been known to be HIF-1α target genes, such as Vegf, Glut1, Phd3/Egln3, Aldoc, Ldha, Gapdh and many more [24]. Furthermore, genes were identified that have recently been shown to be direct HIF-1α-target genes, including Axl [245], Angptl4 [72], and multiple jumonji-domain histone demethylases [246]. Additionally, analysis of the gene lists revealed enrichment of several genes in WT cells that are either involved in stem cell maintenance, or are commonly used stem cell surface markers including CD133/Prom1 [117], which has been shown to a HIF-1α target gene, Gata3 [247], Wnt signaling pathway genes such as Wnt10a, Wnt5b, Lrp5, and Fzd7 [248], Notch pathway genes such as Dll1 and Hey1 [164], and Itga6/CD49f.…”
Section: Discussionmentioning
confidence: 99%